“Mushroom in the heart”: a Volvariella volvacea infective endocarditis case report - Mao, Yunhan; Liu, XinPei; Zhang, ChaoJi; Zheng, Jun (Frontiers in Cardiovascular Medicine, 2025)
Volvariella volvacea (V. volvacea), an edible mushroom, may act as a pathogenic agent causing invasive fungal infections (IFIs) in immunocompromised patients. We present a 38-year-old male with persistent high fever post-allo-HSCT. Plasma mNGS revealed rising V. volvacea DNA loads (1,137 copies/μl). Intravenous antifungal therapy was initiated upon the diagnosis of IFI. Transthoracic echocardiography showed a 4 × 1 cm left atrial vegetation, with enhanced CT confirming multiorgan septic emboli (brain and kidney). PET/CT revealed a left atrial vegetation originating from a right lung infectious lesion, spreading contiguously into the left atrium via the pulmonary vein. Urgent vegetation resection was performed, followed by continued intravenous antifungal treatment. At the 5-month follow-up, the patient was afebrile with negative mNGS, completely resolved pulmonary lesion, and an improved quality of life. This case highlights the potential value of surgical-targeted antifungal therapy for fungal endocarditis and suggests practical principles: including mNGS-guided diagnosis, urgent surgical excision, long-term optimized antifungal therapy, and regular follow-up surveillance of the residual infected lesion.